Thinking about thinking cognition, science, and psychotherapy - McDowell, Philip E. (Routledge/Taylor & Francis Group, 2015)
This book examines cognition with a broad and comprehensive approach. Drawing upon the work of many researchers, McDowell applies current scientific thinking to enhance the understanding of psychotherapy and other contemporary topics, including economics and healthcare. Through the use of practical examples, his analysis is accessible to a wide range of readers. In particular, clinicians, physicians, and mental health professionals will learn more about the thought processes through which they and their patients assess information.